FINANCIAL LITERACY: THE IMPACT ON THE PROFITABILITY OF THE SMEs IN KUCHING - Shafinah, Rahim; Vinod, Raj Balan (Universiti Malaysia Sarawak, 2020)
This study aims at investigating the financial knowledge, financial behaviour and the attitude towards finance amongst on small medium entrepreneurs (SMEs) in Kuching. More specificallyon how these powerful factors affect the profitability on fast growingbusiness enterprises in largest city in the Borneo Island over the last decade. The research takes a descriptive approach fitting its underlying pursue and draws interesting conclusions with over 75% response rate. Analysis of the data collected clearly reveals that the knowledge of finance in general relates significantly stronger to the bottom line of these business entities relative to the owners’financial attitude and their ensuing behaviour towards financial decision making. Therefore, small medium entrepreneurs are highly recommended to participate in financial education on a regular basis to keep them well informed and equipped with the latest ways of managing the finances of their businesses to ensure better financial planning, execution and monitoring of enterprises that inevitably will lead to increased and sustainable earnings.